Ion beam induced atomic transport in bilayer systems - Son, JH; Kim, TG; Chang, GS; Whang, CN; Song, JH; Chae, KH (ELSEVIER SCIENCE BV, 2002)
Atomic transport in ion beam mixed CO/Pt and Pd/Au bilayer systems have been studied from the shifts of maker layers in Rutherford backscattering spectroscopy. Thin layers (I rim) of marker (Pd for Co/Pt and Ni for Pd/Au) were embedded as markers at each interfaces. 80 keV At+ was used to irradiate the marker samples at the temperature range between 90 and 600 K. The CO/Pt system shows isotropic atomic transport (J(Co)/J(Pt) similar to 1.1) at low temperatures and anisotropic atomic transport (J(Co)/J(Pt) similar to 5.0) at high temperatures. Meanwhile, the Pd/Au system shows near isotropic atomic transport (J(Pd)/J(Au) similar to 1.2) at all temperatures examined. These results were discussed in terms of the activation energies for the normal impurity diffusion, cohesive energy difference, and the vacancy migration energy. Atomic transport in thermal spike regime is closely related with the activation energy for normal impurity diffusion. In radiation enhanced diffusion regime, the cohesive energy and/or the vacancy migration energy plays a dominant role for the atomic transport. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: RADIATION-ENHANCED DIFFUSION